IMPLEMENTASI INTERNET OF THINGS PADA SISTEM MONITORING SUHU, KELEMBABAN DAN KEBERADAAN API PADA RUANG SERVER PT XYZ - Sari, Nita Winda; Attaqwa, Yusita (Jurnal Inkofar, 2024)
PT. XYZ is a company engaged in technology which, apart from being a hosting and domain service provider, is also an internet service provider. Therefore, server performance is very much considered in supporting the performance of hosting and internet services. In order to maintain the stability of server performance and the hardware in it, controlling temperature, humidity and the presence of fire in the server room is very important for the pic server. However, there are several things that become an obstacle that a pic server is not always in the server room, while problems can occur outside of pic server working hours or control hours. This research aims to create a monitoring system for temperature, humidity and fire in the server room that can be accessed remotely via the internet and the data is displayed in real time which makes it easier for the pic server in the monitoring process so that at any time the problem will be handled quickly. The method used in this research is the Research and Development (R&D) method. The margin error of the measurement results is for a temperature of 0.91%, humidity 1.42% and the fire sensor is able to read the presence of a fire with a distance of more than 5 meters.